Usulan Peramalan Permintaan & Pengendalian Persediaan Bahan Baku Pada Produk Alternator di PT.XYZ - Agustinus Yunan; Abillah Abdan Gunawan; Oki Widhi Nugroho (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
PT. XYZ is engaged in manufacturing automotive products has products such as altenator and motor starter for automobile vehicles. The problem that exists in the company is experiencing a shortage of products to sell or not being able to meet the demand for the number of products requested. The purpose of this study is to determine optimal production planning and raw material inventory control in order the company can minimize stock outages. The methods used in this study are moving average, weight moving average, and exponential smoothing for forecasting. As for raw material inventory control, it uses the economic order quantity, safety stock, and reorder point methods. The results of this study obtained is weight moving average method n = 3, because it has the smallest error rate, namely with MAD of 5,364, MSE of 39,447,784, and MAPE of 10.66%%. Meanwhile, raw material inventory control for 2022 obtained by using economic order quantity method, achived by directly order 11,243 units per year, with the number of orders every 55 times, then the total inventory cost is IDR 673,725,000. In the safety stock method for 2022, it is 3,564 units with a reorder point of 7,128.